AIE based GSH activatable photosensitizer for imaging-guided photodynamic therapy. Issue 71 (6th August 2020) - Zhang, You-Hui; Li, Xue; Huang, Li; Kim, Hyeong Seok; An, Jusung; Lan, Minhuan; Cao, Qian-Yong; Kim, Jong Seung
Abstract : A GSH activatable photosensitizer with aggregation-induced emission characteristics for imaging-guided photodynamic therapy of cancer cells. Abstract : A novel ferrocene decorated vinyl pyridinium-substituted tetraphenylethylene (TPEPY-S-Fc ) linked by a disulfide bond was designed as a GSH activatable photosensitizer by aggregation-induced emission for imaging-guided photodynamic therapy of cancer cells.